Effect of Drying Methods on Chemical Composition of Spinach “Aieifo” (Amaranthus aquatica) and Pumpkin Leaf (Telfairia occidentalis) and Their Soup Meals - Gladys, H.E. Oguche (Pakistan Journal of Nutrition, 2011)
The study evaluated the effect of drying; methods on chemical composition of spinach, “aleifo” (Amaranthus aquatica) and pumpkin leaf (Telfairia occidentalis) and their soup meals. The two vegetables were purchased from local market in Unale-Ibaji Local Government Area, Kogi State, Nigeria in bulk. These two vegetables were washed, cleaned, plucked from the stalk and processed to mimic traditional methods of preserving vegetables. The vegetables were divided into three equal portions. The first portion served as the control, the second and third portions were sun and shade dried. Aliquots of the dried samples were pulverized, sieved, packaged in polythene bags and kept in cool dry place until used for various chemical analysis. The other dried portions as well as their controls (fresh) were used for preparation of soup meals. The chemical composition of the vegetables and their soup meals were determined using current standard methods. Sun and shade drying drastically reduced moisture content of the vegetables when compared to the controls (84.47-7.80 and 7.42%). The protein for the sun and the shade dried samples were higher than those of the controls (3.50 and 4.70 vs 6.47, 5.50 and 5.77 and 5.44%, respectively) (p